Effectiveness of Dexmedetomidine vs Propofol in Post-Open Heart Surgery Patients: A Prospective, Randomized, Double-Blind Study at the PLA Army Central Hospital in Beijing, China - Shen, Li (HM Publisher, 2024)
Introduction: Dexmedetomidine and propofol are sedation drugs commonly used in patients after open heart surgery. The aim of this study was to compare the effectiveness of dexmedetomidine and propofol in patients after open heart surgery in terms of sleep quality, delirium, and hemodynamics. Methods: A prospective, randomized, double-blind study was conducted on 120 patients after open heart surgery at the PLA Army Central Hospital in Beijing, China. Patients were randomized to receive dexmedetomidine (n = 60) or propofol (n = 60). Sleep quality was measured using the Pittsburgh Sleep Quality Scale (PSQI), delirium was measured using the confusion assessment method for the intensive care unit (CAM-ICU), and hemodynamics were monitored continuously. Results: Patients receiving dexmedetomidine had lower PSQI scores (p < 0.05) and a lower incidence of delirium (p < 0.05) compared with patients receiving propofol. There were no significant differences in hemodynamic parameters between the two groups. Conclusion: Dexmedetomidine is more effective than propofol in improving sleep quality and reducing delirium in patients after open heart surgery.